2014
DOI: 10.7860/jcdr/2014/8929.4648
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Virtual Articulator in Prosthetic and Restorative Dentistry

Abstract: Virtual reality is a computer based technology linked with the future of dentistry and dental practice. The virtual articulator is one such application in prosthetic and restorative dentistry based on virtual reality that will significantly reduce the limitations of the mechanical articulator, and by simulation of real patient data, allow analyses with regard to static and dynamic occlusion as well as to jaw relation. It is the purpose of this article to present the concepts and strategies for a future replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
42
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 11 publications
0
42
0
9
Order By: Relevance
“…The absence of data on non-working side contacts was unavoidable, as virtual modelling of condylar movement was reported to be imprecise (40). Several reports acknowledged that a limitation of available CAD/CAM systems is lack of a reliable virtual articulation system that can simulate dynamic motion (41)(42)(43). The authors therefore concluded that the accuracy of the virtual articulator in simulating dynamic motion might be acceptable for orthodontic treatment but not for prosthodontic treatment (39).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of data on non-working side contacts was unavoidable, as virtual modelling of condylar movement was reported to be imprecise (40). Several reports acknowledged that a limitation of available CAD/CAM systems is lack of a reliable virtual articulation system that can simulate dynamic motion (41)(42)(43). The authors therefore concluded that the accuracy of the virtual articulator in simulating dynamic motion might be acceptable for orthodontic treatment but not for prosthodontic treatment (39).…”
Section: Discussionmentioning
confidence: 99%
“…The articulator, an instrument simulating the position and movement of jaws, has been used as an essential tool in diagnosis, planning, and laboratory procedures in dental treatment. Recently, with the advancement of technology, this dental tool is shifting from a mechanical device to its digital alternative, the virtual articulator . Embedded in computer software, the virtual articulator provides a series of advantages: full analysis of static/dynamic jaw movements and occlusion; detailed visualization of tooth contacts and virtual treatment design; and ability to be integrated with other digital workflows in dentistry such as digital smile design, computer‐assisted implant planning, and digital maxillofacial surgery planning…”
mentioning
confidence: 99%
“…Digital alternatives to the conventional facebow have been proposed and studied with mixed results . Problems still exist relating patient‐specific data to the transverse axis and esthetic reference planes, and most do not address the edentulous arch or if no verifiable interocclusal position is present; however, there are few issues with relating the maxillary arch to the cranial base.…”
mentioning
confidence: 99%
“…Problems still exist relating patient‐specific data to the transverse axis and esthetic reference planes, and most do not address the edentulous arch or if no verifiable interocclusal position is present; however, there are few issues with relating the maxillary arch to the cranial base. The axis can be located by stereophotogrammetry, anatomic landmarks, mathematical calculation of an instantaneous axis, reverse engineering and collision avoidance, or electronic jaw movement analyzers . Alignment of the maxillary and mandibular virtual casts to the virtual articulator and simulation of mandibular movements is the ultimate goal.…”
mentioning
confidence: 99%
See 1 more Smart Citation